(untitled) (Research, Society and Development, 2024)
Objective: The objective of this study was to investigate the opinion of patients at the Santo Onofre Family Health Unit, the Pioneiros Catarinense Family Health Unit, the Cancelli Basic Health Unit and the Vila Tolentino Basic Health Unit (all in the municipality of Cascavel-PR, Brazil) about the dress of doctors during consultations. Methodology: A questionnaire was carried out with these patients in order to collect information and analyze their preference for the clothes worn by medical professionals and their impact on the doctor-patient relationship, especially on aspects such as safety, trust and competence, which are passed on from the doctor to the patients through the clothes worn by the professional. Results: There was a significant preference for wearing a lab coat, which was associated with greater comfort by the patients, and the interviewees were unbiased when it came to social and casual clothing, analyzing issues such as quality of care, competence and accessibility. Conclusion: The cultural aspects of the population and the clinical context of care, in this case in Basic Health Units, have a major influence on the patient’s preference for medical attire.